PENGARUH STRATEGI PENYULUHANDAN TINGKAT STATUS SOSIAL EKONOMITERHADAP PENGETAHUAN NELAYANTENTANG KOSERVASI PESISIR PANTAI (Sebuah Eksperimen di Kecamatan Telukbetung Barat, Kota Bandar Lampung) - Sutrisno, Eddy (Jurnal Ilmiah Pendidikan Lingkungan dan Pembangunan, 2017)
This study aims to determine the effect of counseling strategies and levels of socio economic status of knowledge about the conservation of coastal fishermen. The method used in this study is an experiment with 2 x 2 factorial design. The study population was fishing in the District of West Telukbetung, Bandar Lampung numbered 32 people. Data analysis technique used is the Two-Way Analysis of Variance followed by Tukkey test. The findings of this study include: 1) Knowledge of the conservation of coastal areas that follow the strategy of grouping extension is higher than that following the classical extension strategy.; 2) For the fisherman with high level of social economic status with knowledge about coastal conservation among groups of fishermen who follow counseling strategies and follow the strategy of grouping classical education. Where the higher is the group of fishermen that high social economic status following the strategy of grouping extension; 3) For the fisherman with a low level of socio-economic status with knowledge about coastal conservation among groups of fishermen who follow the strategy of grouping extension and follow the classical extension strategy. Where the higher is the group of fishermen that low social economic status following the strategy of classical education, and 4) There is interaction effect between education strategy and the level of socio economic status of knowledge on coastal conservation. Based on these findings we can conclude that there is no extension strategies are most effective, depending on background characteristic fishermen and their socio economic status. Therefore, if the selected grouping strategy is appropriate only to fishermen who have a high socioeconomic status, education classical conversely, if the strategy is dominated by the lecture method is chosen, then it is just right for the fishermen who have low socioe conomic status.